Chapter Vie e voci delle diaspore nella narrativa di Claudio Magris - Musarra-Schrøder, Ulla (Biblioteca di Studi di Filologia Moderna, 2021)
Diaspora is one of the most important themes in Claudio Magris' works, including its interrelations with issues of exile, emigration, deportation. The Jewish Diaspora is the main topic of many of Magris' essays and essayistic works, in particular Lontano da dove (1971). In other works, such as Microcosmi (1992) and the great novel Alla cieca (2005), Magris visits other diasporas, such as the exodus of thousands of Italians from Istria and Dalmatia. His recent novel Non luogo a procedere (2015) brings together the Jewish Diaspora and the African Diasporas through centuries of colonization epically and symbolically materialized in the figure of Luisa Brooks, the novel's female protagonist.